Integrated Inventory Model for Single Vendor Multi-Buyer with a Single Item by Considering Warehouse and Capital Constraint - Agustiandi Agustiandi; Yoon Mac Kinley Aritonang; Cherish Rikardo (Department Industrial Engineering, University of Muhammadiyah Malang, 2021)
Integrated inventory management coordinates all party's replenishment policies to provide optimal benefits. Many models have been developed, but none of them have considered capital and warehouse constraints comprehensively. It may cause the model which cannot be applied, since it has exceeded the capacity. This study developed an integrated inventory model that consisted of one vendor, multi-buyer, and one type of item. The main objective was to minimize the joint total expected cost by considering warehouse, capital, and service level constraint. The optimal formula was constructed by using the Lagrange multipliers method. The results showed that with an increment in holding cost, the vendor tends to reduce lot size to minimize joint total expected cost. It is vice versa to the increment in set up cost. An increment in buyer service level can increase lot size and reduce order frequency. The buyer capacity is essential to determine its capability to apply the optimal replenishment policy.